APPLICATION OF THIN LAYER CHROMATOGRAPHY (Tlc) AND GASS CHROMATOGRAPHY-MASS SPEKTROSCOPY (GC-MS) AS ANALYSIS TECHNIQUE OF PHITOSTEROL COMPOUNDS IN WATER EXTRACT OF BEAN FRUIT (Phaseolus vulgaris L.) - Hilyatul Jannah; I Made Sudarma; Yayuk Andayani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
Phytosterols are vegetable sterols, included in secondary metabolite compounds and have broad benefits in the health field. Sources of natural ingredients containing phytosterol compounds have been widely used as medicinal ingredients, one of which is beans (Phaseolus vulgaris L.). This research is an exploratory research, aimed to analyze the content of phytosterol compounds in water extract, and the result of partition of water extract of beans using TLC and GC-MS technique. The result of phytochemical test showed that from 13 extracts of partition result with n-hexane solvent, DCM, ethyl acetate, and methanol, only 5 extracts showed positive steroid, including water extract, hexane residue, DCM residue, methanol extract, and methanol residue. The TLC test results on the hexane residue of the partition from the water extract were suspected as stigmasterol compound because it has the price of Rf = 0.9 equal to the standard Rf compound of stigmasterol, whereas the GC-MS product showed negative phytosterol.